Culturally Adapted Counseling Interventions for University Students: Effectiveness and Implementation Challenges - Faqihudin Faqihudin (P3M STAI Kuningan, 2025)
Background: University students from diverse cultural backgrounds face significant mental health challenges, yet conventional counseling approaches often fail to address culturally specific needs, resulting in underutilization and suboptimal outcomes.Objective: This study investigated the effectiveness and implementation challenges of culturally adapted counseling interventions for university students.Method: A sequential explanatory mixed-methods design was employed. A total of 480 students across five Southeast Asian universities were allocated to either a culturally adapted counseling intervention (CACI) or standard counseling (SC) condition, with outcomes assessed at baseline, post-intervention, and three-month follow-up. Additionally, 102 stakeholders, including students, counselors, administrators, and cultural representatives, participated in qualitative interviews and focus groups.Findings and Implications: Results demonstrated that CACI produced significantly greater reductions in depression, anxiety, and stress symptoms compared to SC, with large effect sizes ranging from 0.74 to 0.82. Improvements in quality of life, academic self-efficacy, and career confidence were also observed, with benefits maintained at follow-up. Cultural background moderated intervention effects, with Indigenous and Middle Eastern students showing the largest gains. However, implementation analysis revealed substantial challenges, including time constraints, limited resources, and inadequate institutional support.Conclusion: These findings provide robust evidence that culturally adapted interventions enhance mental health outcomes while highlighting the necessity of systemic organizational changes to ensure sustainable implementation in university counseling services.